Punishment Beyond the Deportee: The Collateral Consequences of Deportation. (August 2019) - Golash-Boza, Tanya
Deportations from the United States reached record highs in the aftermath of the Great Recession (2007-2009). At the peak of this wave of deportations, over 400, 000 people were deported from the United States—as many in 1 year as in the entire decade of the 1980s. The majority of these deportees have U.S. citizen family members, nearly all of whom continue to live in the United States. Over 90% of these deportees are men, and nearly all are sent to Latin America, creating gendered and raced consequences for specific communities. This article draws from interviews with 27 people from California who experienced the deportation of a family member to provide insight into the effects of deportation on these families. This article builds on scholarship on the collateral consequences of incarceration to enhance our understanding of the collateral consequences of deportation. The findings reveal that family members face short, medium, and long-term consequences in the aftermath of a deportation and that many adolescents are forced to make an abrupt transition to adulthood when one or both of their parents is deported.